Symmetry energy in nuclear density functional theory - Nazarewicz, W.; Reinhard, Paul-Gerhard; Satuła, W.; Vretenar, D. (European Physical Journal A, 2014)
The nuclear symmetry energy represents a response to the neutron-proton asymmetry. In this paper we discuss various aspects of symmetry energy in the framework of nuclear density functional theory, considering both non-relativistic and relativistic self-consistent mean-field realizations side by side. Key observables pertaining to bulk nucleonic matter and finite nuclei are reviewed. Constraints on the symmetry energy and correlations between observables and symmetry energy parameters, using statistical covariance analysis, are investigated. Perspectives for future work are outlined in the context of ongoing experimental efforts. © The Author(s) 2013.
CRIS-Team Scopus Importer:2023-07-24